Improving the efficacy of the lean index through the quantification of qualitative lean metrics - Oleghe, Omogbai; Salonitis, Konstantinos (Elsevier, 2015)
Multiple lean metrics representing performance for various aspects of lean can be consolidated into one holistic measure for lean, called the lean index, of which there are two types. In this article it was established that the qualitative based lean index are subjective while the quantitative types lack scope. Subsequently, an appraisal is done on techniques for quantifying qualitative lean metrics so that the lean index is a hybrid of both, increasing the confidence in the information derived using the lean index. This ensures every detail of lean within a system is quantified, allowing daily tracking of lean. The techniques are demonstrated in a print packaging manufacturing case.
Keywords: Lean metirc; lean performace; lean index; qualitative analysis; quantitative analysis